The Analysis of the Effects of Olfactive Stimulus in Learning in Context of Educational Technology - Akpinar, Burhan; Ozdas, Faysal; Yildirim, Bilal; Batdi, Veli (Elsevier Science Bv, 2013)
When the educational Technologies, which are used in the process of learning-teaching process, are associated with sensory organs, the least used one becomes the olfactive stimuli. Nowadays, because of being foreground of visual-audio Technologies, Positivism is based on vision and audition but it ignores the other senses. Although seeing and hearing play important roles, the ineffectiveness of other senses is delusion in this process. In this delusion the impact of visual-audio Technologic devices from telescope to television, internet, mobile phones is inevitable. However sensation and learning is wholistic and based on togetherness of five senses. Thus, with the delusion olfactive stimulus which is rejected from the educational field is effective on senses, attention, concentration and memory in learning. The purpose of this study, which is in form literature review, is to discuss the nature of olfactive stimulus the effectiveness in education, areas of usage in context of educational technology, to deduce and to make suggestions. (C) 2013 The Authors. Published by Elsevier Ltd.
13th International Educational Technology Conference -- OCT 30-NOV 01, 2014 -- Lisbon, PORTUGAL
Keywords: Olfactive stimulus; Olfactive educational technology; Sense of smell and learning